ANALISIS PEMODELAN PENGUJIAN EKSISTENSI ANOMALI RETURN HARIAN DI BURSA EFEK INDONESIA (STUDI KASUS PERIODE 2005-2008) - Setyawasih, Rianti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2009)
This paper investigates the day-of-the-week effect in Indonesia Stock Exchange (IDX) returns and conditional variance (volatility) front October 2005 to October 2008. The empirical research was conducted using the AR, ARCH, and GARCH model and not the usual linear regression method. The results obtained indicate the GARCH (1,1) model is capable to capture the most empirical features observed in stock return data (leptokurtosis, skewness and volatility clustering); the results also shows the signifcant presence of the day-of-the-week effect on both stock returns and volatility.